Comparison of the interactions in the rare gas hydride and Group 2 metal hydride anions - Harris, Joe; Manship, Daniel; Breckenridge, William; Wright, Timothy G. (American Institute of Physics, 2014)
We study both the rare gas hydride anions, RG–H− (RG = He–Rn) and Group 2 (Group IIa) metal hydride anions, MIIaH− (MIIa = Be–Ra), calculating potential energy curves at the CCSD(T) level with augmented quadruple and quintuple basis sets, and extrapolating the results to the basis set limit. We report spectroscopic parameters obtained from these curves; additionally, we study the Be–He complex. While the RG–H− and Be–He species are weakly bound, we show that, as with the previously studied BeH− and MgH− species, the other MIIaH− species are strongly bound, despite the interactions nominally also being between two closed shell species: M(ns2) and −(1s2). We gain insight into the interactions using contour plots of the electron density changes and population analyses. For both series, the calculated dissociation energy is significantly less than the ion/induced-dipole attraction term, confirming that electron repulsion is important in these species; this effect is more dramatic for the MIIaH− species than for RG–H−. Our analyses lead us to conclude that the stronger interaction in the case of the MIIaH− species arises from sp and spd hybridization, which allows electron density on the MIIa atom to move away from the incoming H−.